As características do gênero demonstrativo em Cícero, Horácio e Quintiliano: The characteristics of the demonstrative genre in Cicero, Horace and Quintilian. - Rodrigues de Abreu Carvalho, Luíza Helena (Rónai – Revista de Estudos Clássicos e Tradutórios, 2015)
O presente trabalho é fruto de um ano de pesquisa acerca das características do gênero epidítico nas obras De oratore de Cícero, Ars poetica de Horácio e na Institutio oratoriade Quintiliano. Considerando que os três autores viveram em momentos distintos, tanto temporal como social e politicamente, tentamos mostrar a importância do gênero para os contextos e como o epidítico passou de marginalizado a essencial na Roma Antiga. Abstract The research which this paper is based on looks at the different roles of the epidectic genre in Cicero’s De Oratore, Horace’s Ars Poetica and Quintilian’s Institutio Oratoria. Since these three authors lived under different literary, social and political conditions, some of the goals of this paper are to show how the importance of the genre changed under each of those conditions and how essential the once marginalized epidectic genre came to be in Ancient Rome. Keywords: epideitic genre; Cicero; Horace; Quintilian